Hyperspectral outcrop models for palaeoseismic studies. (23rd December 2019) - Kirsch, Moritz; Lorenz, Sandra; Zimmermann, Robert; Andreani, Louis; Tusa, Laura; Pospiech, Solveig; Jackisch, Robert; Khodadadzadeh, Mahdi; Ghamisi, Pedram; Unger, Gabriel; Hödl, Philip; Gloaguen, Richard; et al.
Abstract: The traditional study of palaeoseismic trenches, involving logging, stratigraphic and structural interpretation, can be time consuming and affected by biases and inaccuracies. To overcome these limitations, a new workflow is presented that integrates infrared hyperspectral and photogrammetric data to support field‐based palaeoseismic observations. As a case study, this method is applied on two palaeoseismic trenches excavated across a post‐glacial fault scarp in northern Finnish Lapland. The hyperspectral imagery (HSI) is geometrically and radiometrically corrected, processed using established image processing algorithms and machine learning approaches, and co‐registered to a structure‐from‐motion point cloud. HSI‐enhanced virtual outcrop models are a useful complement to palaeoseismic field studies as they not only provide an intuitive visualisation of the outcrop and a versatile data archive, but also enable an unbiased assessment of the mineralogical composition of lithologic units and a semi‐automatic delineation of contacts and deformational structures in a 3D virtual environment. Abstract : To overcome the limitations of the traditional study of palaeoseismic trenches, a new workflow is presented that integrates infrared hyperspectral and photogrammetric data. This method was applied on two palaeoseismic trenches excavated across a post‐glacial fault scarp in northern Finnish Lapland. The hyperspectral imagery (HSI) was corrected and co‐registered to a structure‐from‐motion point cloud. The resulting HSI‐enhanced virtual outcrop models provide an intuitive visualisation and archive of the outcrop, and enable an unbiased assessment of its mineralogical composition. Résumé: L'étude traditionnelle des tranchées paléosismiques, impliquant l'enregistrement des coupes et l'interprétation stratigraphique et structurelle, peut prendre beaucoup de temps et être entachée de biais et d'inexactitudes. Pour surmonter ces limites, une nouvelle méthodologie est présentée, intégrant des données photogrammétriques et hyperspectrales infrarouges en appui aux observations paléosismiques de terrain. Comme étude de cas, cette méthode est appliquée à deux tranchées paléosismiques creusées à travers un escarpement de faille post‐glaciaire dans le nord de la Laponie finlandaise. L'imagerie hyperspectrale (HSI) est corrigée géométriquement et radiométriquement, traitée à l'aide d'algorithmes classiques de traitement d'images et d'apprentissage machine, et recalée sur un nuage de points photogrammétrique. Les modèles virtuels d'affleurements améliorés par HSI constituent un complément utile aux études paléosismiques de terrain, car ils fournissent non seulement une visualisation intuitive de l'affleurement et une archive de données facile d'emploi, mais permettent également une évaluation non biaisée de la composition minéralogique d'unités lithologiques ainsi qu'une délimitation semi‐automatique des contacts et des structures de déformation dans un environnement virtuel 3D. Zusammenfassung: Die traditionelle Protokollierung und stratigraphische/strukturelle Interpretation paläoseismischer Gräben kann zeitaufwendig sein und durch Verzerrungen und Ungenauigkeiten beeinflusst werden. Um diese Einschränkungen zu überwinden, wird ein neuer Arbeitsablauf vorgestellt, der hyperspektrale und photogrammetrische Daten integriert, um feldbasierte paläoseismische Beobachtungen zu unterstützen. Als Fallstudie wird diese Methode auf zwei paläoseismischen Gräben angewendet, die über eine postglaziale Verwerfung im nördlichen finnischen Lappland angelegt wurden. Das hyperspektrale Bild wird geometrisch und radiometrisch korrigiert, mit etablierten Bildverarbeitungsalgorithmen und maschinellen Lernverfahren verarbeitet und mit einer fotogrammetrischen Punktwolke verknüpft. Hyperspektrale Aufschlussmodelle sind eine sinnvolle Ergänzung zu paläoseismischen Feldstudien, da sie nicht nur eine intuitive Visualisierung des Aufschlusses ermöglichen und ein vielseitiges Datenarchiv darstellen, sondern auch erlauben, die mineralogische Zusammensetzung lithologischer Einheiten zu ermitteln sowie Kontakte und Deformationsstrukturen in einer virtuellen 3D‐Umgebung zu analysieren. Resumen: El estudio tradicional de las trincheras paleosísmicas, que implica la anotación, la interpretación estratigráfica y estructural, puede llevar mucho tiempo y verse afectado por sesgos e inexactitudes. Para superar éste hándicap, se presenta un nuevo flujo de trabajo que integra datos hiperespectrales infrarrojos y fotogramétricos para apoyar las observaciones paleoseísmicas de campo. Como caso de estudio, este método se aplica en dos trincheras paleosísmicas excavadas a través de una cornisa post‐glacial en el norte de la Laponia finlandesa. Las imágenes hiperespectrales (HSI) se corrigen geométrica y radiométricamente, se procesan utilizando algoritmos de procesamiento de imágenes establecidos y aproximaciones de aprendizaje automático, y se hacen corresponder sobre una nube de puntos derivada por fotogrametría. Los modelos de afloramiento virtual mejorados con HSI son un complemento útil para los estudios de campo paleosísmicos, ya que no solo proporcionan una visualización intuitiva del afloramiento y un archivo de datos versátil, sino que también permiten una evaluación imparcial de la composición mineralógica de las unidades litológicas y una delineación semiautomática de contactos y deformación en un entorno virtual 3D. 摘要: 传统的古地震沟研究, 包括测井、地层和构造解释, 通常耗时并易受偏差和不准确性的影响。为了克服这些限制, 本研究提出新的工作流程, 整合红外高光谱和摄影测量数据, 以辅助古地震的现场观测。本研究以芬兰拉普兰北部的冰川期后断层陡坡上开挖的两块古地震沟, 作为研究案例。高光谱图像（HSI）经过几何和辐射校正, 使用既有的图像处理算法和机器学习方法分析, 并与由运动恢复结构所得点云进行配准。 HSI增强的虚拟露头模型是古地震现场研究的有效补充, 因为其不仅提供露头的直观可视化和多类型的数据存档, 而且能够对岩性单元的矿物组成, 在三维虚拟环境中进行无偏评估与半自动区分。